2014
DOI: 10.1158/2326-6066.cir-13-0133
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Expression on Peripheral Blood Cells Increases with Stage in Renal Cell Carcinoma Patients and Is Rapidly Reduced after Surgical Tumor Resection

Abstract: Programmed Death-1 receptor (PD-1) is an inhibitory receptor on hematopoietic cells that can negatively regulate immune responses, particularly responses to tumors, which often upregulate PD-1 ligands. PD-1/PD-1 ligand blocking antibodies can reverse the inhibition and show significant therapeutic promise in treating renal cell carcinoma (RCC), lung cancer and melanoma. While PD-1 expression on tumor infiltrating lymphocytes has been associated with poor outcome in RCC, we sought to define immune cell biomarke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
112
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 50 publications
8
112
1
Order By: Relevance
“…In these studies the expression of PD-1 was detected in PB NK cells derived from patients 37,38,59,60 but not from HDs. In addition, the level of expression reported was very low, thus rendering it difficult to discriminate between PD-1 1 and PD-1 2 cells and to identify a distinct subset of PD-1 1 cells.…”
Section: Discussionmentioning
confidence: 79%
“…In these studies the expression of PD-1 was detected in PB NK cells derived from patients 37,38,59,60 but not from HDs. In addition, the level of expression reported was very low, thus rendering it difficult to discriminate between PD-1 1 and PD-1 2 cells and to identify a distinct subset of PD-1 1 cells.…”
Section: Discussionmentioning
confidence: 79%
“…Signaling downstream of PD-1 is mediated by the presence of an immunoreceptor tyrosine-based switch motif (ITSM) and an immunoreceptor tyrosine-based inhibitory motif (ITIM) that recruit anti-SRC homology phosphatase (SHP)-1 and SHP-2 protein tyrosine phosphatases to modulate inhibitory signaling [Nirschl et al 2013;MacFarlane et al 2014]. PD-1 is inducibly expressed on CD4+ and CD8+ T cells, NK cells, B cells and monocytes within 24 h from their immunological activation [Keir et al 2008].…”
Section: Introductionmentioning
confidence: 99%
“…The migration, invasion, conglutination and growth analyses of cancer cells are the most commonly used methods to judge cytoactivity. These methods can reflect the fact that the tumor leaves the primary tumor extracellular matrix (11)(12)(13)(14)(15). In the present study, it was found that the reproduction rate of the tumor cells was relatively low in the early passage.…”
Section: A B C D E F Discussionmentioning
confidence: 99%
“…At present, a number of studies have confirmed that PD-1 is a synergistic inhibitory receptor, which can regulate T cell proliferation (12,22). The antigen-stimulated high expression of PD-1 on the CD8 + T-cell surface is associated with T-cell depletion.…”
Section: A B C D E F Discussionmentioning
confidence: 99%